Utilization of synthetic wastewater in experimental teaching for activated sludge process - Bùi Minh Triết (Journal of Technical Education Science, 2018)
Activated sludge process plays an important role in the curricula of enviromental majors. The implementation of activated sludge experiments with real wastewater shows many drawbacks: health hazards, poor control of wastewater composition, potential accidents. Synthetic wastewater can be an effective alternative for real wastewater in the instruction of activated sludge experiments. This paper presents some recommendations on composition and application of synthetic wastewater for experimental teaching for activated sludge process. The recommendations focus on the choice of carbon source; BOD5:N:P ratio; concentrations of trace elements; the storage of synthetic wastewater; potential effects of synthetic wastewater on teaching process.